Cookies are required for login! Check our privacy consent banner for more details.

Suppose f is a polynomial such that f(0) = 47, f(1) = 32, f(2) = -13, and f(3)=16. What is the sum of the coefficients of f?

Thanks my dudes!

Hmm...well......I could be wrong here, but here's what I was thinking:

Since f(0) = 47 , we know that the constant term is 47 .

Since f(1) = 32 , we know that the sum of the coefficients + 47 = 32

the sum of the coefficients + 47 = 32 so

the sum of the coefficients = -15

Your logic is spot on!